Hubungan Antara Pola Asuh Orang Tua Dengan Perilaku Seksual Pada Remaja Di Komunitas Rohani Kota Malang - Asba , Ilsa Ismail; Firdaus, Achmad Dafir; Kurniawan, Andi Surya (Jurnal Keperawatan Muhammadiyah, 2025)
Background: Adolescence is a transitional period from childhood to adulthood, marked by various complex physical and emotional changes, including behaviors such as attraction to the opposite sex, which then triggers sexual urges. Sexual behavior refers to all actions driven by sexual desire towards the opposite sex. Parenting patterns within the family hold a strategic value in shaping a child's personality and play a very important role in adolescent development.Objective: To examine the relationship between parenting patterns and sexual behavior among adolescent congregants in the city of Malang. Methods: This study used an analytic design with a cross-sectional approach. The population in this study consisted of 100 individuals, using total sampling techniques. Data analysis was conducted using univariate and bivariate analysis with the Chi-Square test. Results: Univariate analysis showed that nearly half (49%) of adolescents in one community at a house of worship in the City of Malang had democratic parenting from their parents. Furthermore, more than half (51%) of adolescents in the same community exhibited risky sexual behavior. Bivariate analysis found a significant relationship between parenting patterns and sexual behavior among adolescents, with a p-value = 0.000. Conclusion: Adolescents who receive permissive and authoritarian parenting tend to have riskier sexual behavior compared to those who receive democratic parenting. Parenting patterns are influenced by parental education; the higher the parents' education level, the better the type of parenting provided to their children.